Contradiction and Aphairesis in Plato’s Republic - Gutiérrez, Raúl (Peitho. Examina Antiqua, 2015)
The purpose of this paper is to show that Plato uses contradictions in the Republic as an impulse to think and to advance in the ascent to the Idea of the good. The procedure to dissolve the main contradictions in the text is that of aphairesis, complementary to that of prosthēsis. Also if they are explicitly named just at the beginning and at the end of the ascent (Books II and VII), I will show that aphairesis and prosthēsis are consistently applied throughout the ascendant argument of Republic I-VII. Starting with the separation of the opposites at the sensible level, the process will continue separating the rational and the irrational in the soul and culminate when explicitly naming the aphairesis of the One/Good at the intelligible level. As will be seen, the opposites in question are unity and indeterminate/indefinite multiplicity. But also if named, the culminating aphairēsis of the Idea of the Good will not be consistently developed in the Republic. Some important allusions to it will also be found in the Parmenides allowing us to solve the main unresolved contradictions in the Republic in consonance with the theory of principles of the agrapha dogmata.